Interspecies Chemical Signals Released into the Environment May Create Xenohormetic, Hormetic and Cytostatic Selective Forces that Drive the Ecosystemic Evolution of Longevity Regulation Mechanisms - Burstein, Michelle T. (International Hormesis Society, 2011)
Various organisms (i.e., bacteria, fungi, plants and animals) within an ecosystem can synthesize and release into the environment certain longevity-extending small molecules. Here we hypothesize that these interspecies chemical signals can create xenohormetic, hormetic and cytostatic selective forces driving the ecosystemic evolution of longevity regulation mechanisms. In our hypothesis, following their release into the environment by one species of the organisms composing an ecosystem, such small molecules can activate anti-aging processes and/or inhibit pro-aging processes in other species within the ecosystem. The organisms that possess the most effective (as compared to their counterparts of the same species) mechanisms for sensing the chemical signals produced and released by other species and for responding to such signals by undergoing certain hormetic and/or cytostatic life-extending changes to their metabolism and physiology are expected to live longer then their counterparts within the ecosystem. Thus, the ability of a species of the organisms composing an ecosystem to undergo life-extending metabolic or physiological changes in response to hormetic or cytostatic chemical compounds released to the ecosystem by other species: 1) increases its chances of survival; 2) creates selective forces aimed at maintaining such ability; and 3) enables the evolution of longevity regulation mechanisms.